Testing the bivariate mixture hypothesis using German stock market data - Robert C. Jung; Roman Liesenfeld (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1996)
According to the bivariate mixture hypothesis (BMH) as proposed by Tauchen and Pitts (1983) and Harris (1986,1987) the daily price changes and the correspond-ing trading volume on speculative markets follow a joint mixture of distributions with the unobservable number of daily information events serving as the mixing variable. Using German stock market data of 15 major companies the distributional properties of the BMH is tested employing maximum-likelihood as well as generalized method of moments estimation techniques. In addition to providing a new approach for the pointwise estimation of the latent information arrival rate based on the maximum-likelihood method, we investigate the time-series properites of the BMH. The major results can be summarized as follows: (i) the distributional characteristics of the data (esp. leptokurtosis and skewness in the distribution of price changes and volume re-spectively) cannot be explained satisfactorly by the BMH; univariate mixture models for price changes and trading volume separately reveal a possible specification error in the model; (ii) a univariate normal mixture model can account for the observed distributional characteristics of price changes; (iii) the estimated process of the latent information rate cannot fully explain the time-series characteristics of the data (esp. the volatility clustering or ARCH-effects).
Keywords: 330